Pemecatan Pelaksana Wasiat Dan Peran Balai Harta Peninggalan - Putra, Morly Samantha Dione; Latumeten, Pieter Everhardus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The dismissal of the Executor of the Will follows the rules for the dismissal of a guardian in Indonesia. Guardianship in Indonesia is inseparable from the rules of family law. In this case, it can be carried out by the Balai Harta Peninggalan which oversees supervising the Executor of the Will who has been appointed by the Heirs in dividing and separating their inheritance to the heirs. In the mentoring process, it does not deny that the Executor of the Will commits fraud and is not in accordance with his work responsibilities so that the full heirs of the ab intestato can apply for the dismissal of the Executor of the Will in accordance with the rules in article 1022 of the Civil Code. With the support of statements of experts quoted from interviews which state that the expulsion of the Executor of the Will can be submitted by all heirs ab intestato. Dismissal can be carried out if the executor of the will does not want to carry out his duties, or he carries out his duties half-heartedly. This is regulated in Article 1022 of the Civil Code. Meanwhile, in relation to the role of the Balai Harta Peninggalan, the BHP has the authority to oversee the implementation of the will and propose the dismissal of the Executor of the Will if the will is not implemented.